Adding the latency period to a muscle contraction model coupled to a membrane action potential model - Kappaun, Nadia Roberta Chaves; Graça, Ana Beatriz Nogueira Rubião; Lavinas Gonçalves, Gabriel Benazzi; Weber dos Santos, Rodrigo; Vecchio, Sara Del; Bastos, Flávia Souza (Frontiers in Physics, 2023)
Skeletal muscle is responsible for multiple functions for maintaining energy homeostasis and daily activities. Muscle contraction is activated by nerve signals, causing calcium release and interaction with myofibrils. The importance of understanding muscle behavior is its impact on medical conditions, like in presence of some diseases and its treatment, such as cancer, which can affect muscle architecture, leading to deficits in its function. For instance, its known that radiotherapy and chemotherapy also has effects on healthy tissues, leading to a reduction in the rate of force development and the atrophy of muscle fibers. The main aim is to reproduce the behavior of muscle contraction using a coupled model of force generation and the action potential of the cell membrane, inserting the latency period observed between action potential and force generation in the motor unit. Mathematical models for calcium dynamics and muscle contraction are described, incorporating the role of calcium ions and rates of reaction. An action potential initiates muscle contraction, as described by the Hodgkin-Huxley model. The numerical method used to solve the equations is the Forward Euler method. The results show dynamic calcium release and force generation, aligning with previous research, and the time interval between membrane excitation and force generation was accomplished. Future work suggests simulating more motor units at the actual scale for the possibility of comparison with real data collected from both healthy individuals and those who have undergone cancer treatment.